Her voice in the forest: a neo-archetypal ecofeminist analysis of Sang Kancil as the female mousedeer - Quah, Christopher Wai Kheong; Anita Harris Satkunananthan, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Sang Kancil, as a trickster mousedeer figure, may be seen as a cultural artefact according to Benedict Anderson's theory of Imagined Communities. Sang Kancil is traditionally seen as male in Malaysian folklore but, in more contemporary retellings, has been re-envisioned as a female trickster. These adaptations reflect socio-cultural changes which incorporate ecocritical perspectives. Therefore, this article interrogates these contemporary retellings through the lens of ecofeminism while creating new categories of neo-archetypes based on Neo-Archetypal Theory. Using contemporary revisionings of Sang Kancil: Sang Kancil & The Crocodiles by Huseinah Madihid (2016), Trick or Tree by M. Shan Mughalingam (2011), and the Millie the Mousedeer series by Robert Kanner (2014), this study looks into how the female mousedeer embodies traits of the teacher, nurturer, and magician. By shifting from the traditional Trickster archetype introduced by Jungian psychoanalysis to a more expanded scope of categories available under Neo-Archetypal Theory, this article interrogates the ways in which the female mousedeer necessitates a diversifying of the Neo-Magician archetype. The expected findings from this paper include understanding the ways in which the female Sang Kancil embodies the Neo-Magician archetype by revealing the role of the feminine in nature as a symbol of empowerment, leadership, and education. The implications of this study lead to a better understanding of the evolution of cultural artefacts over time to be more diverse and gender-inclusive.